Caught in the Middle: Empowerment in Middle Managers - Doty, Noelle (Kansas State University. K-State Libraries, 2017)
Previous studies on the topic of middle management focus on how these specific managers drive the organizations they are a part of, how they motivate their subordinates to work effectively and efficiently, how middle managers create excitement, and how their leadership style helps their followers find purpose in their work. And yet, little is done to flesh out how these strong MMs are created, what motivates them, and how they succeed in their position (Kominis & Emmanuel, 2007). These MMs are the “basis of strategic renewal” in bettering an ever-changing organizational environment and, conversely, can even “sabotage implementation efforts” in the changing strategy of the workplace (Mantere, 2008, p. 294). This paper aims to discover what factors influence the empowerment of middle managers for the purpose of better understanding and development of MMs in organizational and workplace structures. Motivation is the influence on a person’s “direction, vigor and persistence of action” (Rajhans, 2012, p. 82). The current literature on the subjects of management, motivation, and work performance focus on the topics of role expectations, and empowerment, and are typically viewed through the theoretical lenses of structural empowerment and psychological empowerment, which are outlined below.
Citation: Doty, N. (2017) Caught in the Middle: Empowerment in Middle Managers. Unpublished manuscript, Kansas State University, Manhattan, KS.
Kirmser Undergraduate Research Award - Individual Non-Freshman Category, grand prize